Role of mPRα (PAQR7) in progesterone-induced Ca2+ decrease in human vascular smooth muscle cells. (October 2019) - Pang, Yefei; Thomas, Peter
Abstract : We have shown progesterone exerts a direct action on vascular smooth muscle cells (VSMCs) to induce relaxation through activation of membrane progesterone receptor alpha (mPRα)-dependent signaling pathways, but information on downstream events is lacking. Progesterone-induced changes in calcium concentrations in human umbilical artery VSMCs through mPRα-dependent signaling pathways and the involvement of Rho/ROCK signaling were investigated. Acute in vitro treatment with progesterone and the selective mPRα agonist 10-ethenyl-19-norprogesterone (Org OD 02-0, 02-0) blocked the rapid prostaglandin F2α-induced calcium increase. This inhibitory progesterone action was prevented by knockdown of mPRα but not by knockdown of the nuclear progesterone receptor, confirming it is mediated through mPRα. The decrease in calcium levels and VSMC relaxation were abolished by treatment with FPL64176 (Ca 2+ channel activator), supporting a role for decreased calcium channel activity in this progesterone action. The reduction in calcium was attenuated by pretreatment with pertussis toxin, 8-Bromo-cAMP and forskolin, indicating this progesterone action involves activation of an inhibitory G protein and downregulation of cAMP-dependent signaling. Inhibition of MAPK and Akt signaling with PD98059 and ML-9, respectively, prevented the progesterone-induced calcium concentration decrease and VSMC relaxation. Forskolin decreased progesterone-induced MAPK and Akt phosphorylation which suggests that the cAMP status influences calcium levels indirectly through altering these signaling pathways. Progesterone and 02-0 treatments decreased RhoA activity and ROCK phosphorylation, which suggests that reduced RhoA/ROCK signaling is a component of the mPRα-mediated progesterone actions on VSMCs. The results suggest that progesterone induces VSMC relaxation by reducing cellular calcium levels through mPRα-induced alterations in multiple signaling pathways.